Multi-functional role of grassland systems in the ecological restoration of mines, landfills, roadside slopes and agroecosystems - Pastor J.; Hernández A.J. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Grassland sites of the Mediterranean region of central Spain were analysed as reference systems for restoring several scenarios: (i) abandoned mines with polluted soils; (ii) old urban waste landfills; (iii) roadside slopes; and (iv) degraded agroecosystems with eroded soils. At all the sites, we found pasture plants with multiple functions such as providing soil cover and adapting to water, salt and heavy-metal stresses, as well as acting as a reservoir for native Mediterranean grassland flora. Species growing in the mine soils were mainly Graminaceae, and this plant family was found to accumulate substantial quantities of Zn and other heavy metals. Pasture species capable of stabilizing soils on roadside slopes were: Dactylis glomerata, Cynodon dactylon, Medicago sativa and Plantago albicans. Plant covers containing several legumes, installed to combat soil erosion and increase N in olive and vine crop systems, achieved good cover and did not compete for the water available to the crops.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)